2015
DOI: 10.1007/s00359-015-1025-4
|View full text |Cite
|
Sign up to set email alerts
|

Facultative thermogenesis during brooding is not the norm among pythons

Abstract: Facultative thermogenesis is often attributed to pythons in general despite limited comparative data available for the family. While all species within Pythonidae brood their eggs, only two species are known to produce heat to enhance embryonic thermal regulation. By contrast, a few python species have been reported to have insignificant thermogenic capabilities. To provide insight into potential phylogenetic, morphological, and ecological factors influencing thermogenic capability among pythons, we measured m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It has further been suggested that the intracardiac separation may support the increased metabolism associated with reproductive thermogenesis in pythons (Wang et al, 2003). However, thermogenesis is not ubiquitous within the python phylogeny (Brashears and DeNardo, 2015) and indeed, is absent in the subject of this study, Python sebae (Vinegar et al, 1970). Conversely, pressure separation has been established in all pythons investigated, including evolutionarily divergent species ; T.W., unpublished results).…”
Section: Evolutionary Perspectivesmentioning
confidence: 60%
“…It has further been suggested that the intracardiac separation may support the increased metabolism associated with reproductive thermogenesis in pythons (Wang et al, 2003). However, thermogenesis is not ubiquitous within the python phylogeny (Brashears and DeNardo, 2015) and indeed, is absent in the subject of this study, Python sebae (Vinegar et al, 1970). Conversely, pressure separation has been established in all pythons investigated, including evolutionarily divergent species ; T.W., unpublished results).…”
Section: Evolutionary Perspectivesmentioning
confidence: 60%
“…This finding is further supported by Alexander () who found that mother T b approached T chamber (~23°C) when brooding mothers were prevented from basking. This is in agreement with Brashears & DeNardo's () conclusions that facultative thermogenesis is not the norm in python species. The lack of facultative thermogenesis in southern African python is significant since P. natalensis is a large‐bodied species with a range that extends into the cooler parts of South Africa.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of facultative thermogenesis in southern African python is significant since P. natalensis is a large‐bodied species with a range that extends into the cooler parts of South Africa. This supports the hypothesis that facultative thermogenesis has arisen in Python and Morelia independently (see Stahlschmidt et al ., and Brashears & DeNardo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of activity patterns have focused primarily on diurnal lizards; consequently, data on the activity of tropical snakes is lacking (Reed and Rodda 2009), although extensive studies on brooding python thermal biology are available (Ramesh and Bhupathy 2010;Stahlschmidt and Denardo 2010;Stahlschmidt et al 2012;Brashears and Denardo 2015). Snakes generally exhibit seasonal variations in movement and activity patterns (Slip and Shine 1988;Heard et al 2004).…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%